PREVENTION OF OVERWEIGHT AND OBESITY IN CHILDREN OF SCHOOL AGE - Nunes, Nuno (2022)
Rationale: This project focuses on health promotion, in line with international goals to control the prevalence of childhood overweight and obesity in the child and school population. Thus, the following objective was defined for this project: Improve children's knowledge about healthy eating Methods: Given this, and since schools are a privileged place for the promotion of health (and consequent training of the child population and their parents), the target population of this project will be children aged between 6 and 8 years. The project is divided into 5 stages. In first, partnerships are established and information about the project is detailed through meetings with partners In the second stage, health education sessions will be held on the following topics: food wheel; fundamental foods and principles of the Mediterranean diet and foods rich in sugars and processed fats. The third stage focuses on creating healthy lunch boxes and dishes, using fictitious foods. In addition, students will analyse and interpret the labels through the “nutri-score” system, bringing labels they have at home to the sessions. The fourth stage of the project consists of collecting data on the foods that students bring in their lunch boxes. Thus, once a week, during the snack period, the teachers fill in a table showing the foods that students bring in their lunch box, allowing an intervention aimed at the foods that students bring. The last step is the global evaluation of the project. Results: The expected results are the indicators of intervention: percentage of students who correctly analyse and interpret labels, proportion of students who select foods in a healthy way when preparing healthy lunch boxes and dishes. Conclusion: The project focuses on a priority on a global scale, it intends to be the path of empowerment of the most vulnerable groups, considering children as one of these vulnerable groups, being very conditioned by the social determinants that surround them.